Avaliação institucional na educação infantil: a participação das crianças na organização do trabalho pedagógico - Julio Gomes Almeida; Hosana Vanessa Gomes Aguiar de Paiva (EccoS – Revista Científica)
This article presents results of a research conducted at a Municipal Preschool São Paulo and aimed to verify the possibility of including children in the institutional evaluation process developed at the school. Data were collected through bibliographic review and semi-structured interviews with the management team and two teachers of the unit. The research reveals, among other things, that the school researched manage to hear the children and consider their opinion in deciding on the organization of their times and spaces as well as the organization of educational work process.